In vitro Plant Regeneration of Four Local Varieties of Chickpea (Cicer arietinum L.) Grown in Bangladesh - Banu, TA; Sarker, RH; Hoque, MI (Bangladesh Journal of Scientific and Industrial Research, 2011)
In vitro regeneration system was developed through direct organogenesis from decapitated mature embryo explants of locally grown four chickpea varieties, namely, Barichhola-4, Hyprochhola, Binachhola-3 and Binachhola-4. Best response towards multiple shoot regeneration was obtained on MS medium supplemented with 0.5 mg/l BAP, 0.5 mg/l Kn, 0.2 mg/l NAA along with double concentrations of CaCl2 and NH4NO3. However good shoot health and expanded leaf was found on MS medium containing 1.0 mg/l kn. Apart from this, few experiments were conducted with decapitated embryo attached cotyledon. Using this explants highest number of multiple shoots were obtained on MSB medium containing 4× micronutrients of MS medium with 3.0 mg/l BAP and 0.04 mg/l NAA in all four varieties. Shoots regenerated on 1.0 mg/l kn supplemented medium showed good response towards rooting on MS medium supplemented with 0.2 mg/l IBA in all four varieties. It was observed that micrografting is an alternative technique to in vitro rooting in chickpea. Key words: In vitro regeneration; Decapitated embryo; Chickpea. DOI: http://dx.doi.org/10.3329/bjsir.v46i3.9047 BJSIR 2011; 46(3): 379-384